Intratunnel Pressure Measurement in Patients with Carpal Tunnel Syndrome in Vietnam - Dung Tran Trung; Manh Nguyen Huu; Khanh Trinh Le; Thanh Ma Ngoc (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Objective: Measure the intratunnel pressure of carpal tunnel in patients who underwent surgical treatment for carpal tunnel syndrome in Hanoi Medical University Hospital. Patients and method: Prospective cross-sectional study of 33 carpal tunnel syndrome patients (61 hands) treated surgically at Hanoi Medical University Hospital. Measure the preoperative intratunnel pressure with manometer using needle catheter with 3 positions: neutral position, 90º of fl exion and 90º of extension. Results: the average intratunnel pressure was 13.87 ±1.56 mmHg, it increased when wrist at 90º of flexion and 90º of extension (27.60 ± 2.53 and 34.76 ± 3.25, respectively). Conclusion: There is a high intratunnel pressure situation in the carpal tunnel syndrome.